2012
DOI: 10.1111/j.1365-2044.2011.06980.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hypotension headache after uncomplicated caudal epidural injection

Abstract: SummaryA caudal epidural injection was performed on a middle-aged woman for pain in her right foot. Although the procedure was uncomplicated and a good epidurogram was obtained, the patient went on to develop an orthostatic headache with generalised weakness and syncopal episodes that were treated successfully by epidural blood patching. We describe the aetiology, presentation and treatment of spontaneous intracranial hypotension and review the similarities with our patient's clinical presentation. We hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…Goeller et al also demonstrated marked caudal epidural space pressure elevation associated with the bolus injection of a local anesthetic [8]. SIH after an uncomplicated lumbar epidural injection has also been reported [2, 3]. In our patient, several attempts to enter the epidural space with a needle caused us to push much air into the epidural space, which may have exacerbated the changes in epidural pressure.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Goeller et al also demonstrated marked caudal epidural space pressure elevation associated with the bolus injection of a local anesthetic [8]. SIH after an uncomplicated lumbar epidural injection has also been reported [2, 3]. In our patient, several attempts to enter the epidural space with a needle caused us to push much air into the epidural space, which may have exacerbated the changes in epidural pressure.…”
Section: Discussionsupporting
confidence: 52%
“…The leakage location was far from the Tuohy needle puncture levels. During the loss of resistance technique, changes of pressure in the epidural space and an induced dural tear might have explained the cause of the accident, as Thomas and Thanthulage described [2]. Congenital or acquired dural weakness has been reported as a predisposing factor for SIH [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Although 90% of PDPH patients present within first 3 days, presentation could be delayed up to 12 days or if untreated headache can remain with long term CSF leak. 17,18,19,20 Box 2: Common and rare clinical manifestation of CSF leaks 10,15 (These symptoms have been reflected in the International Headache Society (IHS) Diagnostic Criteria (Box 3) caused by low ICP. 4,5,8 ) If the clinical diagnosis of CSF leak has been suspected, radiological investigation and diagnostic studies will greatly facilitate the confirmation of the cause as well as its anatomical location.…”
Section: Clinical Presentation and Diagnosis Of Low Csf Pressure Headmentioning
confidence: 99%
“…On the other hand incidence in post dural puncture headache (PDPH) is not uncommon and could vary (10-30%). 2,8,20,21,22 Diagnostic study In the presence of extradural fluid will helpful to identify the location of the leak, but this is very rare to be effective.…”
Section: Incidence and Differential Diagnosis (Box 5)mentioning
confidence: 99%